Peran Orang Tua Meningkatkan Prestasi Belajar Anak di Jalan Gatot Soebroto Lorong Adinda Kelurahan Mautapaga Kabupaten Ende - Maria Polencis Pere Ri'a (Departement of Mathematics Education, 2023)
This study aims to determine the role of parents in improving children's achievement on Jalan Gatot Soebroto, Lorong Adinda, Mautapaga Village, Ende Regency. The problem in this study is what is the role of parents in increasing children's achievements on Jalan Gatot Soebroto, Lorong Adinda, Mautapaga Village, Ende Regency. This study uses qualitative research based on the use of complete and in-depth information in interpreting data about variables, is non-quantitative in nature and is intended to explore in depth and not extend to phenomena. The method used is the method of interviews, observation and documentation. The findings of this study are that the role of parents in determining student achievement at school is very large. Parents who do not pay attention to their children's education, for example, they are indifferent to their child's learning process, do not pay any attention to their child's interests and needs in learning, do not manage their study time, do not provide or complete learning tools, do not want to know how their child's learning is progressing, the difficulties experienced by their children in learning and others can cause children to be less or even not successful in their studies. Conversely, parents who always pay attention to their children, especially attention to their learning activities at home, make children more active and more enthusiastic in learning because they know that they are not the only ones who want to progress, but their parents also have the desire. the same one. So that the learning outcomes or learning achievements achieved by students are better.